Sense of urban public place safety in war-torn Bab Al-Sharqi in Baghdad City - Mayoof, Hajiyat Shahad Raad (2020)
The physical remains of warfare in Iraqi cities can be clearly seen in the damages to its urban environment. There are many fallouts of this destruction, but safety is a major concern especially in Urban Public Spaces (UPS). Users of UPS perceived them to be unsafe and thus, the goal of this study is to investigate perceived safety of UPS in a war-torn Iraqi city. This study is carried out in Bab Al-Sharqi a neighbourhood in the centre of Baghdad. A mixed-method approach was applied using a questionnaire survey, in-situ observation, archival analysis and artefact analysis as data gathering instruments. The collected data was then subjected to descriptive and inferential statistical analysis. The results show that the sense of safety in UPS of war-torn Iraqi city is significantly related to boring, visually dull, and physical incompatible places. Furthermore, many UPS are perceived more unsafe for women than men. These findings may contribute to the formulation of a set of strategies to mitigate the impact of the post-war period on the urban environment in Iraq.